Survival Impacts of Perineural Invasion on Patients Under Different Radical Hysterectomies Due to Early Cervical Cancer - Wei, Wei-wei; Wang, Huihui; Zheng, Hong; Chen, Jiming; Shi, Ru-xia (Frontiers in Oncology, 2022)
Abstract Objective: Cervical cancer is a common gynecological malignancy. In addition to the open radical hysterectomy (ORH) and laparoscopic radical hysterectomy (LRH), laparoscopic nerve-sparing radical hysterectomy (LNSRH) could be another treatment option since it could preserve urinary, colorectal, and sexual functions. However, LNSRH might result in early cancer metastasis and recurrence due to inadequate tumor resection. Additionally, whether LNSRH should be considered based on perineural invasion (PNI) status remains controversial. To assess different types of hysterectomy on the outcome of early cervical cancer with PIN. Methods: A retrospective study was performed in early cervical cancer patients who received ORH, LRH, or LNSRH between January 2012 and December 2019. Age, FIGO cancer stages, histopathological types, tumor size, histological grade, invasion depth, lymph node metastasis, lymphovascular space invasion, and PNI were documented. Disease-free survival (DFS) and overall survival (OS) were recorded. Results: A total of 174 patients were included, with 33, 69, and 72 patients received LRH, ORH, and LNSRH, respectively. Twenty-one patients (12.1%) had PNI. DFS (P = 0.000) and OS (P = 0.022) periods were shortened in positive PNI patients than in negative PNI patients (P = 0.000 and 0.022, respectively). In patients with positive PNI, lymph node metastasis, but not the surgery type, was an independent risk factor for DFS and OS (P = 0.000). Conclusion: Early cervical cancer patients with PNI had shorter postoperative DFS and OS periods. In these patients, lymph node metastasis, but not the type of hysterectomy, was independently associated with DFS and OS. Keywords: Perineural invasion; cervical cancer; nerve-sparing radical hysterectomy; laparoscopic surgery